Extending The Conversation About Service Co-creation: Integration Of Principles Of Al-bay’ - Khairul Akmaliah Adham; Syadiyah Abdul Shukor; Adlin Masood; Khairunnisa Abd Samad; Nur Sa’adah Muhamad; Mohd Fuaad Said (IIUM Press, 2024)
VOL. 30 NO. 2